PROBLEMATIKA PADA TATARAN TEKS (ANALISIS KEBAHASAAN PADA TATARAN TEKS) - Ai Rosmiati; Gita Sugiarti; Heri Isnaini (Jurnal Kajian dan Penelitian Umum, 2023)
Indonesian has a special function in the midst of national and state life Indonesia which is marked with the function of the Indonesian language as language country and language national. On the basis of this function, the Indonesian language is used in the preparation of manuscripts script service in various institution country. Variety Language Indonesia Which should used in the preparation of the official document is standard Indonesian. As language Indonesian national language is used by all levels of society in Indonesia. However, these two functions have not been fully implemented, causing problems for language Indonesia. Problems that occur in the Indonesian language are marked by errors language, especially written language. The problems discussed in this article are problems with the structure of the text, language errors are the use of language both orally and in writing that offends the factors or rules of grammar that are good and correct according to the spelling rules perfected by EYD.